Comparison of indocyanine green and blue-stained glue for preoperative localization for pulmonary nodules - Jia Lin; Jia Zhang; Ning Wei; An-Le Wu; Long-Fei Wang; Fei Teng; Yu-Tao Xian; Rui Han (Frontiers in Oncology, 2024)
BackgroundIn patients with pulmonary nodules undergoing computed tomography (CT)-guided localization procedures, a range of liquid-based materials have been employed to date in an effort to guide video-assisted thoracoscopic surgery (VATS) procedures to resect target nodules. However, the relative performance of these different liquid-based localization strategies has yet to be systematically evaluated. Accordingly, this study was developed with the aim of examining the relative safety and efficacy of CT-guided indocyanine green (IG) and blue-stained glue (BSG) PN localization.MethodsConsecutive patients with PNs undergoing CT-guided localization prior to VATS from November 2021 - April 2022 were enrolled in this study. Safety and efficacy outcomes were compared between patients in which different localization materials were used.ResultsIn total, localization procedures were performed with IG for 121 patients (140 PNs), while BSG was used for localization procedures for 113 patients (153 PNs). Both of these materials achieved 100% technical success rates for localization, with no significant differences between groups with respect to the duration of localization (P = 0.074) or visual analog scale scores (P = 0.787). Pneumothorax affected 8 (6.6%) and 8 (7.1%) patients in the respective IG and BSG groups (P = 0.887), while 12 (9.9%) and 10 (8.8%) patients of these patients experienced pulmonary hemorrhage. IG was less expensive than BSG ($17.2 vs. $165). VATS sublobar resection procedure technical success rates were also 100% in both groups, with no instances of conversion to thoracotomy.ConclusionsIG and BSG both offer similarly high levels of clinical safety and efficacy when applied for preoperative CT-guided PN localization, with IG being less expensive than BSG.